The approach of sheikh sa` id hawwa in the interpretation of Quranic verses of faith - Haziyah Hussin; Mazlan Ibrahim; Sohirin M. Solihin (Penerbit Universiti Kebangsaan Malaysia, 2013)
Every interpreter or commentator of the Quran applies a different manhaj when interpreting Quranic verses pertaining to aqidalz (faith). Some interpreters rely on the manhaj of tafsir bi al-ma'thur, while others go beyond this approach and turn instead to rational evidences, theology and philosophy In other words, an interpreter's approach in tafsir is a reflection of his trend of thought and faith. Nevertheless, Quranic interpreters in these modern times, including those coming from Islamic movements, present a different approach in this matter Among the renowned personalities that represent these Islamic movements is S'a'id Hawwa who was also an interpreter (D.1985). The present study aims to identify the inanhaj applied or practiced by this prominent figure in his interpretation and analysis of issues in Quranic verses that are related to faith. This study uses content analysis to analyze Sa 'id Hawwa s' interpretation of the Quran in his book al-Asas fi al-Tafsir His interpretation of issues of the Quran that are related to faith are compiled, then analyzed descriptively based on themes. Findings from the study showed that the main issues of interest to Sa 'id Hawwa are about Rublibiyyalz (Unity/Oneness of Allah :s Lordship), Uluhiyyah (Oneness of Worship) and concepts of Islam. Meanwhile issues that are central to his manhaj in his tafsir are those that are related to faith as the central theme of the Quran, the Quran as the primary source of reference about issues pertaining to faith, interpretation of Mutashabihat (unclear and ambiguous) verses based on the madhhab of the Salaf the role of faith in life, and the interrelationship between legislation and faith. The present study also found that the formation of this manhaj was influenced by the involvement of this figure in the Muslim Brotherhood movement and the use of the famous tafsir book Fi Zilal al-Qur 'an as a source of reference for it.